If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + 8)(3y + 20) = 0 Reorder the terms: (8 + 5y)(3y + 20) = 0 Reorder the terms: (8 + 5y)(20 + 3y) = 0 Multiply (8 + 5y) * (20 + 3y) (8(20 + 3y) + 5y * (20 + 3y)) = 0 ((20 * 8 + 3y * 8) + 5y * (20 + 3y)) = 0 ((160 + 24y) + 5y * (20 + 3y)) = 0 (160 + 24y + (20 * 5y + 3y * 5y)) = 0 (160 + 24y + (100y + 15y2)) = 0 Combine like terms: 24y + 100y = 124y (160 + 124y + 15y2) = 0 Solving 160 + 124y + 15y2 = 0 Solving for variable 'y'. Factor a trinomial. (20 + 3y)(8 + 5y) = 0Subproblem 1
Set the factor '(20 + 3y)' equal to zero and attempt to solve: Simplifying 20 + 3y = 0 Solving 20 + 3y = 0 Move all terms containing y to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 3y = 0 + -20 Combine like terms: 20 + -20 = 0 0 + 3y = 0 + -20 3y = 0 + -20 Combine like terms: 0 + -20 = -20 3y = -20 Divide each side by '3'. y = -6.666666667 Simplifying y = -6.666666667Subproblem 2
Set the factor '(8 + 5y)' equal to zero and attempt to solve: Simplifying 8 + 5y = 0 Solving 8 + 5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 5y = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 5y = 0 + -8 5y = 0 + -8 Combine like terms: 0 + -8 = -8 5y = -8 Divide each side by '5'. y = -1.6 Simplifying y = -1.6Solution
y = {-6.666666667, -1.6}
| 10-2x=42 | | (x^2)+8x-15=0 | | 3a+4b-8(4a-5b)= | | 3(x^2)-12x-15=0 | | (x^2)+4x-5=0 | | lnx-ln(x+6)=2 | | 6x-3x^2+24= | | y=6x-3x^2+24 | | .90x=.72y | | (x^2)-18x-19=0 | | 5x+5=x^2-1 | | (x^2)+6x-11=11 | | 4.2/5.6,1.68/2.24= | | 5/2,4/1.6= | | 8/9,12/18= | | x+(x-63)=687 | | 17x-4x+6x= | | -9(4b+3)+(37b-8)=0 | | 65=17-14-4b | | 2.3q-4.9-2.2q=-0.9q-4.8 | | 2x^2-6x-45=0 | | 3x^9+9x^2+x+27=0 | | 6(x^2)+9x=0 | | x^3+2x^2+x+8=0 | | x^3+x^2+x+8=0 | | 6-6x-12=2+2x | | 3x^3+x^2+x+1=0 | | 13t+4t-13t= | | x^3-6x^2-6x+136=0 | | (ab+4a^2b^3)+(4a^2b^3-ab)= | | 4y-24=-20 | | X+.50(6)=.70(x+6) |